P215 A systematic literature review of factors related to mortality in patients with COPD. (11th November 2022) - Gibson, D; Siddiqui, MK; Hurst, JR; Stolz, D; Verma, M; Sharma, S; Holmgren, U
Abstract : Introduction and Objectives: Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide, but the strongest predictors of mortality in patients with COPD are unclear. The objective of this systematic literature review was to assess associations of treatment and comorbidities with mortality in patients with COPD. Methods: A systematic literature review spanning over 15 years (January 2005–December 2020; English-language only) was conducted using Embase, Cochrane and PubMed to examine how 1) inhaled corticosteroid (ICS)- versus non-ICS-containing therapies (including no therapy) and 2) comorbidities impact mortality in patients with COPD. References providing univariate and multivariate analyses were assessed separately. Results: Of 643 identified COPD treatment references, 24 references were included and 18 references (16 studies) had multivariate analyses. Mortality risk was lower with ICS- versus non-ICS-containing therapy across most references ( figure 1 ); 14 references (12 studies) reported statistically reduced risk. For comorbidities, 54 of 6952 identified references were included. Cardiovascular diseases (CVDs) were most frequently observed, with heart failure (estimate [95% confidence interval] range: 1.10 [1.03–1.17] to 2.72 [1.67–4.44]) and arrhythmia (1.30 [1.10–1.60] to 1.56 [1.25–1.96]) independently predicting increased mortality. Conclusions: In COPD, reduced mortality risk was observed with ICS- versus non-ICS-containing therapies. CVD, including heart failure and arrhythmia, was associated with increased mortality risk. Please refer to page A216 for declarations of interest related to this abstract.